The graph of desire : using the work of Jacques Lacan - Eidelsztein, Alfredo (Karnac, 2009)
The graph of desire is one of the principal points of reference in Lacanian psychoanalysis. In this book the graph is analyzed in its multiple aspects and relations. Step by step, the author reveals and considers formulations from the simplest to the most complex. The treatment of this issue does not deal only with the development and explanation of its logical, mathematical and topological aspects but also goes through the psychoanalytical theory and practice. The author has immersed himself in Lacan's text "The Subversion of the Subject and the Dialectic of Desire in the Freudian Unconscious.